Five-Year Immune Persistence of a Quadrivalent Meningococcal Conjugate Vaccine (MenACYW-TT) and Immunogenicity and Safety of a Booster Dose in Children - Federico Martinón-Torres; Robert Simko; Rolf Ebert; Mika Rämet; Céline Zocchetti; Olga Syrkina; Siham Bchir; Isabelle Bertrand-Gerentes (Infectious Diseases and Therapy)
Abstract Introduction Many countries recommend vaccination against Neisseria meningitidis serogroups A, C, W, and Y in infants and young children to prevent invasive meningococcal disease. We evaluated the immunogenicity and safety of a quadrivalent meningococcal tetanus toxoid-conjugate vaccine (MenACYW-TT) booster in children primed with the same meningococcal vaccine 5 years earlier. Immune persistence following priming vaccination was also evaluated, and the study is ongoing to generate 10 years’ post-priming data. Methods Healthy children, vaccinated with MenACYW-TT 5 years earlier as toddlers, were enrolled. Participants were randomized to receive MenACYW-TT booster (group 1) or no booster (group 2), stratified by country and meningococcal serogroup C (MenC) vaccination status (primed at age ≤ 1 year vs. naive). Antibodies against each serogroup were measured by serum bactericidal assay using human complement (hSBA). Seroresponse sufficiency at 30 days post-booster was demonstrated if the lower limit of the one-sided 97.5% confidence interval (CI) of the seroresponse rate (proportion of participants with post-vaccination titers ≥ 1:16 when baseline titers were < 1:8 or with a ≥ fourfold increase when baseline titers were ≥ 1:8) was > 75% for each serogroup. Seroprotection rates (proportion with hSBA titers ≥ 1:8) and geometric mean titers (GMTs) for each serogroup were also assessed. Results A total of 209 participants were enrolled across 26 sites in Finland, Germany, Hungary, and Spain (group 1, n = 93; group 2, n = 116). Five years post-priming, GMTs, and seroprotection rates were higher than those observed before priming vaccination in both groups, indicating long-term persistence. Booster seroresponse rates in group 1 for all serogroups ranged from 93.2% to 98.9%, with seroresponse sufficiency demonstrated (lower limit of one-sided 97.5% CIs for the seroresponse rates ranging from 85.7% to 93.8%). Seroprotection rates and GMTs post-booster increased across all serogroups, with nearly all participants seroprotected, suggesting adequate booster response. Seroresponse was comparable between MenC-primed and MenC-naive participants. No new safety concerns were identified. Conclusions MenACYW-TT provides long-term immune persistence and a robust immune response when administered as a booster in children primed 5 years earlier. Trial Registrations Clinicaltrials.gov, NCT04936685; EudraCT: 2021-000104-38; WHO: U1111-1255-4941. Graphical abstract available for this article. Graphical Abstract